Respuesta :

Answer:

( 3x − 1) ( 5x^2 + 2 )

Step-by-step explanation:

15x^3 − 5x^2 + 6x − 2

= ( 3x − 1) ( 5x^2 + 2 )

Using factorization by grouping, the resultant expression is [tex](5x^{2} +2)(3x-1)[/tex].

What is factorization by grouping?

Factorization by grouping means that we need to group the terms with common factors before factoring.

[tex]= 15x^{3} - 5x^{2} + 6x-2\\ =5x^{2} (3x-1)+2(3x-1)\\=(5x^{2} +2)(3x-1)[/tex]

Learn more about factorization by grouping here

https://brainly.com/question/27742891

#SPJ2